Variation in human performance in the hypoxic mountain environment - Martin, D. S.; Levett, D. Z. H.; Grocott, M. P. W.; Montgomery, H. E. (Experimental Physiology, 2010)
Ascent to altitude is associated with a fall in barometric pressure, and with it a decline in the partial pressure of atmospheric (and thus alveolar) oxygen. As a result, a variety of adaptive physiological processes are engaged to mitigate the fall in tissue convective oxygen delivery which might otherwise occur. The magnitude and nature of such changes is also modified with time, a process known as acclimatization. However, other phenomena are at work; the ability to perform physical work at altitude falls in a manner which is not wholly related to changes in arterial oxygen content. Indeed, alterations in local skeletal muscle blood flow and metabolism may play an axial role. Thus, for those who are not native to high altitude, the ability to compete at altitude is likely to be impaired. The magnitude of such impairment in performance, however, differs greatly between individuals, and it seems that genetic variation underpins much of this difference. The identification of the relevant genetic elements is in its infancy in humans, but ongoing work is likely to help us gain an increasing understanding of how humans adapt to altitude and to develop mitigating interventions.